Public-private partnership for earthquake mitigation involving retrofit and insurance - Yao, Xijun; Wei, Hsi-Hsien; Shohet, Igal M.; Skibniewski, Mirosław J. (Technological and Economic Development of Economy, 2015)
Public-Private Partnerships involving governments and insurers have been used worldwide for mitigation of natural-hazards. However, the implementation of such systems in developing countries presents problems for their key stakeholders. On the one hand, property owners are hesitant to purchase insurance or invest in retrofit projects due to cost considerations. On the other hand, insurers are reluctant to cover potential seismic losses, because of uncertainties about the risk. This study introduces an innovative Public-Private Partnership framework for property owners, insurers and governments to facilitate decisions related to hazard insurance and structural retrofit of vulnerable buildings. This framework can also help insurance firms reduce the level of corporate financial assets available for payment of compensation to their clients, as required by regulations aimed at reducing the risk of insurer insolvencies. Property owners are motivated to participate in the framework by extra mitigation subsidies from the government. While the government will be reimbursed for part of the cost of these retrofit projects by insurance firms, whose own savings will be achieved through reductions to legally mandated corporate capital. A case study is presented to demonstrate the feasibility of this approach for mitigating seismic risk to residential buildings in a rural area.